Comparative Analysis of Cross-Platform MAD Frameworks - Verma, Kunal; Maniktala, Digvijay (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Mobile Application Development is getting to be additionally difficult with differing stages and their product improvement packs. Lately, mobile computing has been having truly a revolution. Anyways one of the difficulties that has been conceived due to this revolution is technology and device fragmentation leaving developers stupefied. Platform developers, device manufacturers accompany such a variety of gimmicks and functionalities that it has been hard to give developers a less demanding method for creating applications and running the application on every cell phone with expense and time compelling measures. To lessen the expense of development and connectivity with maximum users across a plethora of platforms, developers are relocating to cross-platform application development tools. In this paper, we give a few choice criteria past the portability concerns toward picking suitable cross-platform solution for application development. Nonetheless, we discovered that cross-platform solutions might be suggested by and large, yet they are still constrained if high prerequisites apply with respect to execution, convenience or native user experience.